Strategi Digital Content Marketing Untuk Meningkatkan Brand Awareness: Studi pada Produk Fesyen Lokal Fashion Today - Aji Aditama; Diana Diana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the digital content marketing strategy implemented by the local fashion brand Fashion Today and its role in building brand awareness in the social media era. This research employs a qualitative descriptive approach with a case study strategy. Data were collected through interviews with the marketing manager, digital content observation, documentation, and consumer questionnaires as supporting data. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that Fashion Today implements digital content marketing through visual consistency, short-form video content, emotional storytelling, and active audience engagement on Instagram and TikTok. This strategy contributes to building brand awareness mainly at the brand recognition stage, while brand recall has not yet been fully achieved. SWOT analysis shows that Fashion Today is positioned in a growth-oriented strategy with strengths in visual aesthetics and content consistency, as well as opportunities arising from the increasing interest in local fashion. This study highlights the importance of visual consistency, emotional relevance, and clear positioning in building brand awareness in the digital fashion industry.